Landsat time series reveal simultaneous expansion and intensification of irrigated dry season cropping in Southeastern Turkey - Philippe Rufin; Daniel Müller; Marcel Schwieder; Dirk Pflugmacher; Patrick Hostert (Journal of Land Use Science, 2021)
Long-term monitoring of the extent and intensity of irrigation systems is needed to track crop water consumption and to adapt land use to a changing climate. We mapped the expansion and changes in the intensity of irrigated dry season cropping in Turkeys Southeastern Anatolia Project annually from 1990 to 2018 using Landsat time series. Irrigated dry season cropping covered 5,779 km² (± 479 km²) in 2018, which represents an increase of 617% over the study period. Dry season cropping was practiced on average every second year, but spatial variability was pronounced. Increases in dry season cropping frequency were observed on 40% of the studied croplands. The presented maps enable the identification of land use intensity hotspots at 30 m spatial resolution, and can thus aid in assessments of water consumption and environmental degradation. All maps are openly available for further use at https://doi.org/10.5281/zenodo.4287661.
Keywords: 330; water resource management; cropping intensity; fallow frequency; irrigation; crop water requirements; Google Earth Engine